α1 Soluble Guanylyl Cyclase (sGC) Splice Forms as Potential Regulators of Human sGC Activity - Sharina, Iraida G. (American Society for Biochemistry and Molecular Biology, 2008)
Soluble guanylyl cyclase (sGC), a key protein in the NO/cGMP signaling pathway, is an obligatory heterodimeric protein composed of one α- and one β-subunit. The α(1)/β(1) sGC heterodimer is the predominant form expressed in various tissues and is regarded as the major isoform mediating NO-dependent effects such as vasodilation. We have identified three new α(1) sGC protein variants generated by alternative splicing. The 363 residue N1-α(1) sGC splice variant contains the regulatory domain, but lacks the catalytic domain. The shorter N2-α(1) sGC maintains 126 N-terminal residues and gains an additional 17 unique residues. The C-α(1) sGC variant lacks 240 N-terminal amino acids, but maintains a part of the regulatory domain and the entire catalytic domain. Q-PCR of N1-α(1), N2-α(1) sGC mRNA levels together with RT-PCR analysis for C-α(1) sGC demonstrated that the expression of the α(1) sGC splice forms vary in different human tissues indicative of tissue-specific regulation. Functional analysis of the N1-α(1) sGC demonstrated that this protein has a dominant-negative effect on the activity of sGC when coexpressed with the α(1)/β(1) heterodimer. The C-α(1) sGC variant heterodimerizes with the β(1) subunit and produces a fully functional NO- and BAY41-2272-sensitive enzyme. We also found that despite identical susceptibility to inhibition by ODQ, intracellular levels of the 54-kDa C-α(1) band did not change in response to ODQ treatments, while the level of 83 kDa α(1) band was significantly affected by ODQ. These studies suggest that modulation of the level and diversity of splice forms may represent novel mechanisms modulating the function of sGC in different human tissues.